Temperature as a circadian timing cue in the visually impaired - Ball, Danny M.; Mann, Samantha S.; Santhi, Nayantara; Speekenbrink, Maarten; Walsh, Vincent (Progress in brain research, 2025)
The daily rise and fall in ambient temperature caused by Earth’s 24-hour rotation may help regulate circadian rhythms in visually impaired individuals. In all mammals, circadian rhythms, the daily cycles of physiology and behavior, are time controlled by the suprachiasmatic nucleus (SCN), the brain’s central clock. The SCN typically synchronizes circadian rhythms with the light/dark cycle through photoentrainment, a process in which specialized retinal cells capture ambient light and transmit this information to the SCN, allowing it to set its phase. Without light input, the rodent SCN’s light-driven circuits can become desynchronized, potentially allowing alternative entrainment signals, such as ambient temperature, to influence central timing. Here, we consider whether a similar mechanism could benefit visually impaired humans who, due to retinal damage, have reduced or absent photic input to the central clock. Visually impaired individuals often experience circadian misalignment, whereby internal rhythms drift out of synchrony with the light-dark cycle, and we suggest that temperature information may mitigate some of this drift. Temperature entrainment could operate through heat shock pathways from the skin, via thermoregulatory brain regions with reciprocal connections to the SCN, or by shifting core body temperature through warm or cold baths, which can alter the phase of clocks in peripheral organs and potentially feedback to adjust central time. Given that temperature is a weaker cue than light, it remains unknown if, and to what extent, it may significantly impact central timing. However, if effective, temperature entrainment in the visually impaired could potentially improve circadian disorders, poor sleep, and adverse health outcomes associated with circadian dysfunction including depression, cognitive decline, and metabolic disorders, which are more prevalent in this population. Research is needed to confirm the long-term effectiveness of temperature as an entrainment cue in the visually impaired population, which may have broader implications for circadian timekeeping in mammals and the role of temperature in the absence of light.